(untitled) (Plant Tissue Culture and Biotechnology, 2026)
Somatic embryogenesis was carried out following in vitro irradiation using the mature embryo of an indigenous rice genotype, Lombur in this study. Different doses of γ- radiation i.e., 10, 20, 30, 40, and 50 Gy were applied on mature embryo-derived embryogenic calli to optimize standard dose levels. The highest callus induction of 97.7% was found on MS medium supplemented with 13.65 μM 2, 4-D under dark conditions. The highest embryogenic calli of 78.42% was observed in MS medium containing 20.47 μM 2, 4-D. These embryogenic calli were transferred to MS medium fortified with 8.8 μM BAP in combination with 0.27 μM NAA and 46.42 % green spots on the calli were found upon transferring into light condition. A maximum of 74.86% of shoots were obtained on the same medium. The highest healthy rooted plantlets were shown on MS medium supplemented with 4.0 μM NAA. The threshold level was estimated 33 Gy using the survival rate of embryogenic calli for the production of plantlets. Subsequent development of calli i.e. inoculated embryogenic calli, the survival rate of calli, green spots, regeneration frequency, and plantlet survived after callus induction was strongly negatively correlated with gamma irradiation. A successful somatic embryogenesis protocol has been established and irradiation doses for embryogenic calli has been optimized. Plant Tissue Cult. & Biotech. 36(1): 117-127, 2026 (June)